Revisiting the Potential Impact to the Rest of the Caribbean from Opening US-Cuba Tourism - Acevedo Mejia, Sebastian; Alleyne, Trevor; Romeu, Rafael (Washington, D.C. : International Monetary Fund, 2017)
The Cuban revolution and the subsequent US embargo on Cuba helped shape the tourism sector in the Caribbean, facilitating the birth and growth of alternative destinations. Therefore, the apprehension of the Caribbean tourism industry towards a change in US travel policy to Cuba is understandable, but likely unwarranted. The history of tourism in the region has shown that it is possible for all destinations to grow despite large changes in market shares. Our estimations show that liberalizing US-Cuba tourism could result in US arrivals to Cuba of between 3 and 5.6 million, most of it coming from new tourists to the region. We also identify the destinations most at risk of changes in US-Cuba relations.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Tourism Industry; Tourism; Tourist; WP; United States